Ion beam intensity distribution in ion-bombarded areas of biological targets - Yu L.D. (2014)
The ion beam intensity distribution in an ion-beain-bombarded area is particularly important for treating biological targets that are location-sensitive to ion energy and fluence. In order to investigate the beam intensity distribution, we carried out a theoretical calculation. The theoretical study was started from an assumption of a certain 3-D distribution of the beam intensity for a fixed beam spot and was followed by integration to describe a scanning of this beam spot within a certain target area. The details of the calculations with an example of Gaussian distribution for the initial fixed beam spot are presented. The calculated result was compared with an experimentally-measured ion-beam intensity distribution, and good agreement was achieved. The scanning ion-beam intensity distribution was applied to guide ion-beam-induced gene transfer in biological cells such as the bacteria E. coli.